Designing with sketches: the generative effects of knowledge preordering. (28th November 2016) - Brun, Juliette; Le Masson, Pascal; Weil, Benoit
Abstract : Sketches are an essential tool for designers. They allow the externalizing of ideas and are therefore economic cognitively. Sketches also provide the designer with new insights, which play an important role in the emergence of ideas. However, some studies tend to show that sketching does not systematically have a positive effect on idea generation. Our research thus aims to analyze the generative effects of sketches by studying the way sketches support the design strategy of designers. We especially focus on the role of knowledge in comparison with concepts. Three sequences of sketches are analyzed employing C–K design theory; we show that drawings refer to both concepts and knowledge, but mostly to knowledge. In particular, sketching helps the architect mobilize knowledge distant from the initial topic. Moreover, the designer carries out through sketching an important work of knowledge structuration that we call 'knowledge preordering'; by carefully selecting, testing and, if necessary, removing knowledge, the designer organizes a strategically built knowledge space. In particular, all elements involving modularity or determinism in the knowledge basis are abandoned. Such knowledge preordering thus allows the building of a splitting knowledge structure, which offers new rules for concept generation and enhances the production of original and disruptive ideas.